Hedging Transaction and Economic Exposure: A Solution for PT Pura Daya Prima - Ita Puspitasari Mulyono; Michael Suhardianto; Raymundus Parulian Sihotang (Bina Nusantara University, 2009)
Many companies use more than one currency in doing business, which make them being exposed to exchange rate risk fluctuation. Accordingly, the Company’s financial manager needs to understand how to measure the risk exposure in order to determine when and how to protect the company from the risk. PT Pura Daya Prima (PDP) is one of that companies which has long been concerned on how to mitigate its economic and transaction exposure. The purpose of this project is to help the company mitigate its risk exposure and find the best hedging technique or other mitigation strategy to minimize their risk. The result of the project is to determine the most favorable hedging policy and the best way to implement the financial instruments or products available in the market or simulated. It is expected that PT Pura Daya Prima would be able to quickly execute hedging techniques in order to prevent financial loss due to foreign exchange exposure.